Mathematical Critical Thinking Ability Viewed from Students' Habits of Mind in Problem Based Learning Assisted Sevima Edlink - Zuliyanti, Ita; Winarti, Endang Retno; Permatasari, Gilang Anjar (Unnes Journal of Mathematics Education, 2023)
The purposes of carrying out this research were to determine the role of the model Problem Based Learning assisted Sevima Edlink and influence Habits of Mind on the mathematical critical thinking skills of class XI students at SMA Negeri 1 Karanganyar on the basic material of indeterminate integrals. Problem Based Learning assisted Sevima Edlink applied in the learning process in the classroom and integrated into learning resources in the form of student worksheets developed by researchers. Student worksheets developed by researchers have also integrated with contextual approaches and learning models Problem Based Learning with the content of the material and the problems associated with the daily life of students. The research method used in this research was a Mixed Method with models Sequential Explanatory (derivative combination). Activities in this study included learning in class three times for the experimental and control groups, tests of mathematical critical thinking skills for the experimental and control groups, filling out questionnaires for the experimental group, and interviews for the experimental group. The results of this research are Problem Based Learning assisted Sevima Edlink can play a positive role in improving students' mathematical critical thinking skills as shown from the test results and students' mathematical critical thinking skills are also influenced by Habits of Mind. From the research results obtained the learning model Problem Based Learning assisted Sevima Edlink can be one way to improve students' mathematical critical thinking skills. Besides that, it also needs to improve Habits of Mind students, because the higher Habits of Mind students can think critically mathematically will be higher.